Impact of Technological Solutions and Operating Procedures on Odour Nuisance of Municipal Solid Waste Landfills in Poland - A. Kulig; K. Lelicinska-Serafin; G. Sinicyn (Chemical Engineering Transactions, 2010)
Abstract preview not available - see full-text PDF article.